2019
DOI: 10.1038/s41467-019-08451-3
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the origin of two genetic components associated with transposable element bursts in domesticated rice

Abstract: Transposable elements (TEs) shape genome evolution through periodic bursts of amplification. In this study prior knowledge of the mPing/Ping/Pong TE family is exploited to track their copy numbers and distribution in genome sequences from 3,000 accessions of domesticated Oryza sativa (rice) and the wild progenitor Oryza rufipogon. We find that mPing bursts are restricted to recent domestication and is likely due to the accumulation of two TE components, Ping16A and Ping16A_Stow, that appear to be critical for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 51 publications
(87 reference statements)
2
49
0
Order By: Relevance
“…We have benchmarked commonly applied programs for metrics including sensitivity, specificity, accuracy, and precision (Figure 1) and have implemented the optimal set of programs in a comprehensive pipeline called the Extensive de-novo TE Annotator (EDTA). To evaluate each program, we used a high-quality, manually curated library developed for the model species Oryza sativa (rice), which has a long history of TE discovery and annotation [23,3442]. The reference library contains abundant class I and class II elements, making it optimal for testing currently available annotation programs.…”
Section: Resultsmentioning
confidence: 99%
“…We have benchmarked commonly applied programs for metrics including sensitivity, specificity, accuracy, and precision (Figure 1) and have implemented the optimal set of programs in a comprehensive pipeline called the Extensive de-novo TE Annotator (EDTA). To evaluate each program, we used a high-quality, manually curated library developed for the model species Oryza sativa (rice), which has a long history of TE discovery and annotation [23,3442]. The reference library contains abundant class I and class II elements, making it optimal for testing currently available annotation programs.…”
Section: Resultsmentioning
confidence: 99%
“…This was of particular interest because, although all Ping elements are identical, one Ping locus has been implicated in initiating the bursts (9,15). Specifically, PingA_Stow on chromosome (called PingA in this study) was shown previously to be the only Ping shared by the four bursting accessions (9) and found preferentially in the genomes of rice accessions with higher than background mPing copies (15). Taken together, these correlative data suggest that the PingA locus differs from the other Ping loci, perhaps by catalyzing more transposition.…”
Section: Ping Activity At 8 Different Locimentioning
confidence: 99%
“…MITEs are the most abundant TE associated with the genes of higher plants where they populate noncoding regions (introns, 5' and 3' flanking sequences) and are a major contributor to allelic diversity (13,14). While most characterized rice accessions have 0 to 1 Ping and 1-50 mPings (15), the four accessions have 7-10 Pings, ~230-500 mPings, and up to ~40 new mPing insertions per plant/generation (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations